EFFECT OF HAND EXERCISES ON LONG WRITING TASK IN SECONDARY SCHOOL STUDENTS - Dr. KIRAN JESWANI; Dr. TUSHAR J.PALEKAR; Dr. SOUMIK BASU (International Journal of Pharma and Bio Sciences, 2016)
Writing is an essential form of communication in student’s life. Their finger and wrist pain after writing for even a few minutes. A prospective study was conducted to investigate the effect of hand exercises on long writing task in secondary school students. 30 minutes of non-stop copy task followed with 12 sessions of 40-50 minutes exercise each. Number of words written, grip & pinch strength was measured using visual analogue scale (VAS) and hand dynamometer respectively. Visual analogue scale was compared pre and post exercise using paired t-test and correlation between grip, pinch strength and pain reduction using Pearson’s Correlation. P-value (sig. value) from the statistic was 0.000 which is less than 0.05 showed a significant difference in pre and post treatment. Thus it concluded that handwriting speed; pinch and grip strength can be improved after the upper limb exercise program.